2010
DOI: 10.1111/j.1439-0426.2010.01462.x
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of diamond (PA) and square (PE) mesh codends for commercially important fish species in the Antalya Bay, eastern Mediterranean

Abstract: Size selectivity of the 40 mm nominal polyethylene (PE) square mesh codend and the 44 mm nominal polyamide (PA) diamond mesh codend were determined under commercial conditions in the demersal trawl fishery. Data were collected using the covered codend technique and analyzed by logistic equation with a maximum likelihood method. Changing the mesh from a 44 mm PA diamond to a 40 mm PE square increased the mean retention lengths (L 50 s) of red mullet (Mullus barbatus), picarel (Spicara maena) and bogue (Boops bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In this fishery, when selectivity is achieved in only some species, sufficient selectivity is not possible for many other species due to differences in body shape, size and behaviors (Ateş et al, 2010). Skates and rays of all sizes are widely caught in multi-species fisheries and because of their body morphology are not able to escape from the cod end (Enever et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this fishery, when selectivity is achieved in only some species, sufficient selectivity is not possible for many other species due to differences in body shape, size and behaviors (Ateş et al, 2010). Skates and rays of all sizes are widely caught in multi-species fisheries and because of their body morphology are not able to escape from the cod end (Enever et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Estimated selectivity parameters of individual and mean hauls (according to Fryer, 1991) LFM. L50 values of bogue estimated in the present study for all codend are slightly lower from found by Ateş et al (2010) 44 mm PA codend with 300 meshes around the circumferences as 14.2 cm from Antalya Bay. Ateş et al (2010) also presented that changing mesh configuration from diamond to square, L50 values was increase even decrease mesh size from 44 to 40 mm.…”
Section: Discussionmentioning
confidence: 40%
“…On the other hand, Eryaşar et al (2014) estimated L50 values as 6.81 cm and 7.56 cm from hand-woven 300 mesh and 150 mesh in circumference narrow slack knotted codend, respectively. When SRs were compared, the values for 40T1(2.3 cm), 44T1(3.5 cm) and 44T2 (3.0 cm) are close to those determined by Ateş et al (2010) as 3.0 and 2.1 for 44 mm diamond and 40 mm square mesh codend, respectively and Eryaşar et al (2014) as 3.1 and 3.5 cm with standard and narrowed codend, respectively.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The studies carried out to increase the selectivity of bottom trawl net in the Mediterranean Sea showed that square-mesh codend or panels give more chance to juveniles of most species to escape when compared with diamond-mesh codends (Sala et al 2008, Ateş et al 2010, Tokaç et al 2010. Underwater observations carried out by Robertson and Stewart (1988) for bottom trawl codends showed that the mesh has a tendency to close, depending upon increasing catch amount in diamond-mesh codend but in squaremesh codend, the mesh stayed open during the tow.…”
Section: Introductionmentioning
confidence: 99%